Niclosamide Blocks Rice Leaf Blight by Inhibiting Biofilm Formation of Xanthomonas oryzae - Sahu, Sunil Kumar; Zheng, Ping; Yao, Nan (Frontiers in Plant Science, 2018)
Rice (Oryza sativa) is the leading source of nutrition for more than half of the world's population, and by far it is the most important commercial food crop. Rice is one of the most important staple crops around the world. But, its growth and production are significantly hampered by the bacterial pathogen Xanthomonas oryzae pv. oryzae (Xoo) which causes leaf blight diseaserice leaf blight disease caused by the bacterial pathogen Xanthomonas oryzae pv. oryzae (Xoo). Earlier studies have reported the antibacterial ability of FDA-approved niclosamide drug against Xoo. However, the underlying mechanism by which niclosamide blocks the growth of Xoo remained elusive. In the present study, by employing the microbiological, microscopical, molecular, bioinformatics and analytical tools we found that niclosamide can directly inhibit the growth of the Xoo by hampering the biofilm formation and the production of xanthomonadin and exopolysaccharide substances (EPS) required for relentless growth and virulence of Xoo. Interestingly, niclosamide was found to specifically suppress the growth of Xoo without affecting other bacteria like Escherichia coli. Our electron microscopic observations disclosed that niclosamide disrupts the membrane permeability of Xoo and causes the release of intracellular components. Similarly, the molecular docking analysis disclosed the molecular interaction of niclosamide with the biofilm, virulence and quorum sensing related proteins, which was further substantiated by relative gene expression analysis where niclosamide was found to significantly downregulate the expression of these key regulatory genes. In addition, considerable changes in chemical structures were detected by Fourier Transform Infrared Spectroscopy (FTIR) in response to niclosamide treatment. Overall, our findings advocate the utilization of niclosamide as a safe and potent alternative antibacterial compound to control bacterial blight disease in rice.